User needs analysis for a children,s library in barangay UP campus - Kalngan, Michael Lloyd J.; Gonzales, Grace Marie B. (Quezon City : School of Library and Information Studies, University of the Philippines Diliman, 2007)
The study is concerned with the perceptions of Barangay UP Campus community towards the user needs in a children's library in their respective area. A user needs analysis was carried out to determine the answers to this study's main objectives of: (1) finding out the socio-demographic profile of Barangay UP Campus; (2) verifying the perceived user need of children by the members of the community; and (3) establishing the overall view of the community towards establishing a children's library in the barangay.
A survey questionnaire was used as the main research instrument, distributed among 298 legal residents of the barangay. A sample population of 298 households was drawn from a total population of 1,175 households. Each household was represented by one member of that household in the actual survey.
Results of the survey shows that an overwhelming majority (97) of the respondents were in favor of putting up a children's library in the barangay. Concerning the primary needs of children, the most important needs as perceived by the respondents were: (1st) the need for security and (2nd) the need to love and to be loved. Respondents are primarily concerned with the upbringing of the child, thus they prefer education, religion, and health as the top information needs children should be provided of. Ninety-eight percent of the respondents state that books in an integral library resource in a library followed by games and computers. Storytelling was not viewed as an important service in a children's library, with only two respondents agreeing to it.
As determined from the respondents' views and comments, the information needs of children can be sufficiently satisfied if the quality of materials and services is given top priority in a children's library. Although books are traditionally vital in any library, a children's library must also adapt to rapid changes in technology to better carry out its role as an information provider. In the final analysis, the establishment of a children's library in the barangay is earnestly recommended.
Vita.
Thesis (Bachelor of Library and Information Science)--University of the Philippines Diliman
Keywords: Children's libraries -- Philippines -- Quezon City